Deletion of Fgf14 confers resilience to basal and stress-induced depressive-like behavior and reduces anxiety in mice - Francesca Montarolo; Anita Maria Rominto; Luna Berrino; Antonio Bertolotto; Fernanda Laezza; Filippo Tempia; Eriola Hoxha (Translational Psychiatry)
Abstract Depression is a mental illness characterized by despair behavior, inability to feel pleasure, and social withdrawal. Causes are not yet clarified, but stress is a condition that induces depression. Neuronal alterations, comprising maladaptive neuronal plasticity and excitability, are present in both responses to stress and depression. Fibroblast growth factor 14 (Fgf14) controls neuronal excitability and proper action potential firing by stabilizing voltage-dependent sodium (Nav) channels into the axon. Fgf14-Nav channels complex is regulated by glycogen synthase kinase 3. Recently, Fgf14 has been genetically associated to depression. However, little is known about its role in controlling stress-induced depression. This study demonstrates that female Fgf14 −/− mice are resilient to depression, as reported by reduced level of despair behavior, anhedonia, and increased sociability. Also, a reduction of anxious-like behavior was highlighted. Fgf14 −/− mice showed increased expression of cannabinoid receptor without alterations of dopaminergic system in mPFC, suggesting a link between Fgf14 and endocannabinoid system in the control mechanisms underlying depression. Neuronal activity was assessed by analyzing cFOS expression during basal and following acute stress induced by tail suspension test (TST). The analysis revealed that neuronal activation in mPFC and VTA was correlated to immobility, where ratio of cFOS expression over immobility was significantly higher in Fgf14 −/− mice. This suggests that higher neuronal activity might be involved in resilience to depression. In resilient Fgf14 −/− mice, TST-induced acute stress caused activation only in pyramidal neurons. Our findings suggest that Fgf14 is involved in stress-coping mechanisms and could be targeted to improve resilience to depression.